Efficiency of 5% Sodium Hypochlorite in The Removal of Dental Fluorosis Stains: Sodium Hypochlorite against Dental Fluorosis Stains - Rajput, Fozia; Ahmed Siddiqui, Tanveer; Najmi, Naheed; Ravina, .; Khalid, Qasim; Salman, Preesa; Shams, Salman (Pakistan Journal of Health Sciences, 2022)
Dental fluorosis is a specific disturbance in tooth formation, and is defined as a chronic, fluoride-induced condition in which enamel development is disrupted. Objective: To test the efficiency of 5% sodium hypochlorite in removing dental fluorosis stains. Methods: A 5 percent solution of NaOCl was used in each case. It was administered with a cotton applicator to the whole surface of the teeth, and it was repeated until the NaOCl solution had evaporated. After treatment, a follow-up assessment was conducted by a vita shade guide. Results: Patients with dental fluorosis aged 12 to 20 were enrolled in the study. 32 men (59.3%) and 22 women were studied (40.7%). One patient (1.9%) had completed college. There were 23 (42.6%), 23 (42.6%) and 05 (09.3%) cases with inadequate socioeconomic status. One in ten people (or 18.5%) had a family history of fluorosis. 26 (48.1%) brushed once, 23 (42.6%) brushed twice, and just 05 (09.3%) brushed three times. There were 25 mild instances, 15 moderate cases, 10 severe cases, and 4 severe dental cases (DF). 5% sodium hypochlorite was efficacious in 40 (74.1%) and 14 (24.9%) cases of mild to severe dental fluorosis. Conclusion: The 5% sodium hypochlorite was found to be an efficient method for eliminating dental fluorosis lesions in this investigation. Non-invasive and safe procedure for these lesions. No additional supplies are needed, and it may be used on children's permanent teeth with ease. To support the efficacy of a bigger sample size, further studies are recommended.